ANALISIS AKAD MUSYARAKAH PADA PEMBIAYAAN MODAL USAHA BER AGUNAN EMAS DALAM PERSPEKTIF HUKUM ISLAM (Studi Kasus di PT BPRS Mandiri Mitra Sukses Gresik) - salihen, nurus; Suaidi, Amran (Universitas Muhammadiyah Surabaya, 2020)
ABSTRACTIslamic financial institutions have a very large role in the development and growth of the Islamic community, especially in Indonesia in the modern industry. One of them in terms of Musyarakah financing in Islamic banking has been understood as a mechanism that can unite work and capital for the production of goods and services that are beneficial to society . As has been applied in PT BPRS Mandiri a successful partner where the musyarakah financing product uses a gold guarantee within a period of 4 (four) months, and the population is very interested in the customer. From here the authors are encouraged to conduct research on Musyarakah Contract Analysis on Gold Collateral Business Capital Financing in Islamic Law Perspective (Case Study at PT Bprs Mandiri Mitra Sukses Gresik.Based on the results of research at PT BPRS Mandiri Mitra Sukses in terms of financing gold collateral musharaka, it is known that customers are very happy because these residents can help u finance in the customer's business, i.e. in the case of direct funds, they can be disbursed quickly as needed. Then the procedures and requirements are also adjusted to the conditions for the musharaka contract. And not all customers can select the musyarakah financing facility selectively, the bank also provides provisions that only customers have businesses and financial reports. Musharaka financing system is very helpful for micro traders in the market.Â Key Word: Musyarakah contract, Gold Collateral Business Capital Financing, Islamic Law Perspective.